On the Administrative Law Protection of Marine Data Property Rights - Pengfei Bao (Studies in Law and Justice, 2025)
With the rapid development of the marine economy and the swift progress of information technology, marine data, as an emerging factor of production, is increasingly valued. However, there are still many challenges in defining, protecting, and utilizing marine data property rights. This paper aims to explore the administrative law protection of marine data property rights, analyze the legal attributes of marine data property rights, review the current status of marine data property rights protection in China, and draw on international experiences to propose countermeasures for improving the administrative law protection of marine data property rights in China.